Comparative analysis of five mitochondrial genomes of the subfamily Galerucinae (Coleoptera: Chrysomelidae) and evolution of control regions inferred from phylogeny - Xu, Shiwen; Miao, Pu; Liu, Qiaoqiao; Song, Fan; Yang, Hailin; Xia, Zhenyuan; Huang, Weidong (Frontiers in Ecology and Evolution, 2025)
IntroductionMitochondrial genome (mitogenome) is a widely utilized source of genetic data for animal species identification, molecular phylogeny, phylogeography, and evolutionary research at various taxonomic scales. With 14,500 recognized species placed in over 1,100 genera, Galerucinae (Coleoptera: Chrysomelidae), also known as leaf beetles, is the largest subfamily within Chrysomelidae.MethodsWe newly sequenced and annotated five mitogenomes from Galerucinae. Additionally, we investigated their nucleotide composition, codon usage, relative synonymous codon usage and evolutionary rate of protein-coding genes (PCGs). The phylogenetic relationship of Galerucinae also been inferred by gathering mitogenomes of 97 species from GenBank and our newly sequenced five mitogenomes. The divergence times within Galerucinae were estimated using three calibration nodes in MCMCTree. Furthermore, we investigated the structural features of the control regions (CRs) within the phylogenetic framework of Galerucinae.Results and discussionThe length of mitogenomes ranged from 15,737 to 16,484 bp. All of these mitogenomes exhibited high AT content, as well as positive AT skew and negative GC skew. Most PCGs have ATN as their start codons, and TAA and TAG were the most widely assigned stop codons. The substitution rate analysis suggested that ATP8 experienced positive selection, while COX1 underwent purifying selection. Phylogenetic analyses showed that both tribes Alticini and Galerucini were monophyletic sister groups. Within two tribes, most groups and subtribes were monophyletic. Our divergence time inference, dating the origin of Galerucinae to the Middle Cretaceous period (102.69 Ma), and indicated main groups of Galerucinae diverged and occurred during the period from Middle Cretaceous to Middle Paleogene. Finally, we analysis revealed variations in the length and structural organization of the CRs even among closely related groups, which can be attributed to variations in specific structural elements.